Effectiveness of Tobacco Cessation Training Program for primary health care physicians of a South Indian district - Jagannath Purushothama; Sanjeev Badiger; Priyanka Rent; Mackwin D'Mello (Tobacco Induced Diseases, 2018)
Introduction Tobacco Cessation is one of the least attended components of Tobacco Control strategies worldwide. Although there is a felt need by tobacco users to quit the use and Tobacco Cessation Services can be provided in low-resource healthcare settings, lack of adequate training in tobacco cessation among health care physicians acts as a major deterrent to provide the services.